Impact of oral health problems on the quality of life of preschool children: a case–control study. Issue 4 (4th July 2015) - Firmino, Ramon Targino; Gomes, Monalisa Cesarino; Clementino, Marayza Alves; Martins, Carolina Castro; Paiva, Saul Martins; Granville‐Garcia, Ana Flávia
Abstract : Background: There is a need for investigations into the impact of oral problems on OHRQoL with study designs that offer greater strength of evidence. Aim: To evaluate the impact of dental caries and traumatic dental injury (TDI) on the OHRQoL of Brazilian preschool children. Design: A population‐based, matched, case–control study was conducted involving 415 children aged 3–5 years enrolled at public and private preschools. The case group (impact on OHRQoL) and control group (no impact on OHRQoL) were matched for age, sex, and monthly household income at a 1 : 4 ratio (83 cases and 332 controls). Impact on OHRQoL was assessed using the B‐ECOHIS. Dental caries and TDI were determined through clinical oral examinations. Data analysis involved descriptive statistics and conditional logistic regression analysis ( P  ≤ 0.05; 95% CI). Results: The most frequent responses on the B‐ECOHIS were 'felt pain' (79.7%) and 'difficulty in eating' (35.0%). The following variables were significantly associated with impact on OHRQoL: caries severity (OR = 12.58; 95% CI: 5.31–29.79) and TDI (OR: 2.11; 95% CI: 1.23–3.62). Conclusions: Caries severity and TDI impacted the OHRQoL of preschool children.